El lecho en imágenes de la Anunciación (siglos XIV y XV): Interpretación iconográfica según la Patrística Latina - Salvador-González, José María (De Medio Aevo, 2021)
The images of the Annunciation of the 14th and 15th centuries often include in their scene a bed with evident prominence, which allows us to conjecture that this piece of furniture contains some symbolism of particular relevance. Given such unusual detail, this article seeks to interpret the possible doctrinal meanings that this bed could provide. In this sense, twelve Annunciations of this period, which include a bed, are analyzed first with a personal interpretation that stands against some inadequate “interpretations” proposed by other modern authors. We will try to justify our interpretations based on an abundant corpus of texts through which many Latin Fathers and theologians see the thalamus concept as two complementary metaphors: a metaphor of God Son’s incarnation in Mary's womb, and also a metaphor of Mary’s virgin divine motherhood.